Poplar wood-water slurry liquefaction in the presence of formic acid catalyst - Yilgin, M; Pehlivan, D (Pergamon-Elsevier Science Ltd, 2004)
In this study, the liquefaction of a poplar wood slurry in water with the presence of a formic acid (HCOOH) catalyst was investigated by considering the temperature, reaction time and wood particle size as the basic parameters. The experiments were continued until maximum oil yields were attained at different temperatures (250, 300 and 350 degreesC) and showed that oil yields generally increased with temperature, but only up to a maximum value at each temperature and then were reduced. It was found that the particle size did not affect the liquefaction process, but loading the wood into the reactor as a slurry in water positively affected and increased the oil yields. It was concluded that this increment resulted from the prior penetration of the water into the wood particles. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: wood; liquefaction; formic acid